2021
DOI: 10.18805/lr-4374
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Association Studies for Yield and Yield Related Traits in Pigeonpea [Cajanus cajan (L.) Millsp.]

Abstract: Background: Study of phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) reveals the extent of phenotypic and genotypic variability in given population, respectively. Correlation and path analysis helps in identifying suitable selection criteria for improving the crop yield.Methods: Plant material comprised of 68 genotypes belongs to early maturity group of pigeonpea and experiment conducted during Kharif 2015-16 in randomized complete block design with two replications. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Although negative direct effect on seed yield was seen in case of BPP (-1.975), PH (-1.089) and DM (-0.469). The findings are in concurrence to the reports of Sharma et al (2021) wherein it was emphasized that selection for yield enhancement could be made through direct selection for DF and indirect selection for BPP. The results are suggestive that the above morphological i.e.…”
Section: Path Coefficient Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Although negative direct effect on seed yield was seen in case of BPP (-1.975), PH (-1.089) and DM (-0.469). The findings are in concurrence to the reports of Sharma et al (2021) wherein it was emphasized that selection for yield enhancement could be made through direct selection for DF and indirect selection for BPP. The results are suggestive that the above morphological i.e.…”
Section: Path Coefficient Analysissupporting
confidence: 88%
“…Biometrical analysis of a population through genotypic and phenotypic coefficient of variances, correlation study, path coefficient analyses, heritability and genetic advance explicates the underlying variability existing in a population empowering plant breeders to identify the reliable yield attributing characters for which selection would be effective (Singh et al 2019). This further helps in selecting potentially better performing lines from the population on the basis of the reliable yield and yield attributing characters as identified from the biometrical analyses (Pushpavalli et al 2017 andSharma et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ajay et al(2014) observed a high heritability and genetic advance as per cent mean in pigeonpea for the traits viz., plant height, primary branches per plant, the number of pods per plant, seed yield per plant and shelling per cent. Sharma et al(2021) reported high heritability and genetic advance as per cent of mean for traits viz.,the number of primary branches per plant, the number of pods per plant, 100 seed weight and single plant yield in pigeonpea. The most appropriate method to estimate the diversity within any crop species is the D 2 statistics (Bhandari et al, 2017;Priyanka et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Hence agronomic fortification of zinc can be done through soil and foliar applications. The use of micronutrient in pigeonpea is one of the ways to boost up the productivity and to improve the seed quality parameters (Sharma et al, 2010) [12] . The plants exhibited lower rate of protein synthesis and protein accumulation under zinc deficiency.…”
Section: Introductionmentioning
confidence: 99%